Evaluation of transportation network reliability during unexpected events with multiple uncertainties - El Khoury, John (2016)
Measuring transportation network reliability in destabilizing events is a complex task because an accurate modeling requires the inclusion of uncertainty in both the infrastructure and the users' behavior. This paper presents an approach for evaluating the performance reliability, considering the uncertainty in both demand and supply sides of the road network due to an unexpected event. These uncertainties are likely due to the effect of natural disasters on road networks. On the supply side, in addition to link capacity, environment parameters of roads, which indirectly influence parameters of link travel time, are degraded after disasters. Road environment parameters, such as visibility, geometric, pavement condition, and safety elements, impact road capacity by a perceived increased cost or inability to travel. A generalized link travel cost is suggested to capture these effects. On the demand side, elastic demand is modeled with lognormal distribution and a logit-based stochastic user equilibrium is formulated to presents the traveler's uncertain behavior in route choice. In this study, the first order second moment reliability method is used to evaluate network reliability. This paper presents a numerical example that shows the result of ignoring uncertainties after a disaster is overestimated. Also, it was observed that increasing variation of demand and supply decreases the network performance and network reliability, and the increasing knowledge of the user in route choice behavior increases the network efficiency.